Strategi Kreativitas Guru PAI Dalam Pembelajaran Berdiferensiasi untuk Mengatasi Kejenuhan Belajar Siswa Pada Materi Fiqih Shalat - Subayil (Lembaga Bale Literasi, 2025)
This study aims to describe the creativity of Islamic Religious Education (PAI) teachers in implementing differentiated learning to overcome student learning boredom in the fiqh of prayer (fiqih shalat) material for Grade XI students at MA Da’watul Khaer. This research is motivated by the low levels of students’ motivation, participation, and enthusiasm, which are caused by monotonous learning methods that insufficiently consider differences in students’ learning characteristics. Learning boredom is indicated by a decrease in students’ concentration and engagement during the learning process. This study uses a qualitative approach with a descriptive type. Data were collected through observation, interviews, and documentation involving Islamic Religious Education teachers and Grade XI students. Data analysis was carried out through data reduction, data display, and conclusion drawing. The validity of the data was ensured through source triangulation and technique triangulation. The findings of the study show that the creativity of PAI teachers in implementing differentiated learning is carried out through various instructional methods, the use of audio-visual media, grouping students based on ability levels, direct practice of prayer movements, educational games, and the assignment of tasks based on students’ interests and abilities. These strategies are able to improve students’ motivation, active participation, and understanding of the fiqh of prayer material, as well as reduce learning boredom. Supporting factors include institutional support, teacher creativity, and students’ enthusiasm, while the inhibiting factors consist of limited learning facilities and differences in students’ ability levels. This study concludes that differentiated learning is effective in creating Islamic Religious Education learning that is active, enjoyable, and meaningful.